Relationship between psychological capital and depression in Chinese physicians: The mediating role of organizational commitment and coping style - Sun, Li; Zhang, Yuan; He, Jingyun; Qiao, Kexin; Wang, Ce; Zhao, Shuai; Zhao, Jinxin; Qiu, Xiaohui; Yang, Xiuxian; Zhou, Jiawei; Bu, Tianyi; Hu, Xiaomeng; et al. (Frontiers in Psychology, 2022)
Background: It is well known that the medical profession is a high-risk practice, with intense work and complex situations. The physicians are prone to suffer from depression due to occupational stress under high workloads for long periods of time. Depression not only impairs physicians’ mental health, but also affect the quality of health services, so it is important to explore the factors and mechanisms affecting depression among physicians. Methods: In this cross-sectional study, 1139 physicians from Heilongjiang Province were surveyed by cluster sampling procedures. The questionnaires included Psychological Capital Questionnaire, Chinese Employee Organizational Commitment Questionnaire, Trait Coping Style Questionnaire and Self-rating Depression Scale. Pearson correlation analysis and Bootstrap were used for statistical analysis. Results: This study found that 41.6% of physicians suffering from depression. Among them, 17.0% of physicians showed moderate depression, 2.6% of physicians exhibited severe depression. The serial-multiple mediation of organizational commitment and positive coping styles in the relationship between psychological capital and depression was significant. Conclusion: The results showed that psychological capital was sequentially associated with increased organizational commitment, and then increased positive coping styles, which resulted in reduced depression among physicians.